2020
DOI: 10.1080/10408398.2020.1786003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding functionality of sucrose in cake for reformulation purposes

Abstract: We review the functionality of sucrose during the manufacture of cakes from the perspective of sugar replacement. Besides providing sweetness, sucrose has important functionalities concerning structure formation. These functionalities also need to be mimicked in reformulated cakes. First, we review the hypotheses, concerning the development of structure and texture of cakes during manufacturing, which are conveniently summarized in a qualitative way using the Complex Dispersed Systems methodology. Subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 100 publications
1
19
0
Order By: Relevance
“…In agreement with these observations, we have recently shown that the starch paste viscosity associated with gelatinization and swelling decreases with an increase in Mw and/or concentration of the fibres present [13]. However, cohesiveness and resilience should be negatively affected by inhibition of starch swelling and amylose leaching [32,64]. Most likely, these adverse effects were compensated for by the ability of the increasing β-glucans to form cross-links with the starch via hydrogen bonding, thus reinforcing the elastic properties of the starch gel network [65,66].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In agreement with these observations, we have recently shown that the starch paste viscosity associated with gelatinization and swelling decreases with an increase in Mw and/or concentration of the fibres present [13]. However, cohesiveness and resilience should be negatively affected by inhibition of starch swelling and amylose leaching [32,64]. Most likely, these adverse effects were compensated for by the ability of the increasing β-glucans to form cross-links with the starch via hydrogen bonding, thus reinforcing the elastic properties of the starch gel network [65,66].…”
Section: Discussionsupporting
confidence: 79%
“…The technique provides insights into the visco-elastic properties of the dough (G' and tan δ) as affected by key phase transitions such as gluten thermosetting and starch gelatinization. These transitions largely control the structure formation during baking of dough and other cereal-based matrices [14,16,29,32]. In general, three main phases can be observed with regard to the changes in G' as a function of temperature (Figure 3).…”
Section: Dough Thermo-mechanical Properties During Temperature Sweepmentioning
confidence: 99%
“…This resulted in a potentially more favourable texture compared with the WPC cupcake; however, these differences had limited effect on the sensory profile. Cake crumb is formed by a two gel-forming system: starch swelling and gelatinisation, and a protein network denaturation and coagulation, both contributing to cake texture (firmness and cohesiveness) [ 31 , 32 , 33 ]. Hence, it is hypothesised that the HS-WPC powder could have influenced the formation of the starch-filled protein network as a result of the HS-WPC protein particles aggregating with exposed thiol groups, as well as interactions with other sulfhydryl groups from the egg or gluten.…”
Section: Discussionmentioning
confidence: 99%
“…We will describe the ingredients and their transformations using the Complex Dispersed System (CDS) formalism [23], which has already shown its value in describing the functionality of ingredients in potato-based expanded snacks [27], but also in biscuits [29] and cakes [30]. With CDS the structure of the system will be indicated by several symbols, extending the notation commonly used for emulsions, where O/W means oil dispersed into water.…”
Section: Ingredients Structurementioning
confidence: 99%